2017
DOI: 10.1016/j.jneb.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Conversations: Home Preparation of Infant Formula Among a Sample of Low-Income Mothers in the Southeastern US

Abstract: Targeting knowledge or skills gaps and behavioral motivators in the formula-feeding population could positively affect infant-feeding practices that occur outside of recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Low RBP can be a consequence of illness (7), but also reflects conditions of malnutrition when individuals in low-income families have limited access to nutrient-rich foods (810). Whereas, infants in the United States may receive government-funded, vitamin-fortified formulas, comparable support is not given to older children (11). Instead, diets for older children and adults may be calorie-dense and nutrient-poor.…”
Section: Introductionmentioning
confidence: 99%
“…Low RBP can be a consequence of illness (7), but also reflects conditions of malnutrition when individuals in low-income families have limited access to nutrient-rich foods (810). Whereas, infants in the United States may receive government-funded, vitamin-fortified formulas, comparable support is not given to older children (11). Instead, diets for older children and adults may be calorie-dense and nutrient-poor.…”
Section: Introductionmentioning
confidence: 99%
“…The CDC recommends against feeding watered-down formula as it can impair growth and development and result in electrolyte and mineral disturbances (15). Prior to the infant formula shortage, WIC recipients were at risk for watering-down infant formula to increase their allocated supply (23). Contributory factors include the structure of WIC which is a supplemental program that only partially provides infant formula to families at no cost.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review that did not include Japanese reports, at least 11 studies showed that formula was given to children without being prepared according to the prescribed concentrations [3]. Observational studies on formula feeding have reported the addition of cereal to baby bottles in the USA [4]. Moreover, in Brazil, formulas prepared by parents of lower socioeconomic status contained less protein and fat, suggesting that the prepared formula was diluted more than prescribed (i.e., with lower than prescribed concentrations of the formula) [5].…”
Section: Introductionmentioning
confidence: 99%